Promoting Students' Understanding of the Concept of Pressure: Active Learning Environment versus Traditional One - Tural, Güner (Universitas Pendidikan Indonesia, 2020)
One of the topics students have understanding difficulties in science is pressure. The study investigates the effectiveness of an active-learning environment on the students' understanding of the concept of pressure. The sample consisted of 30 students from a public secondary school in Turkey. This study used a pre-test, post-test, quasi-experimental research design with a control group. Ten lessons were conducted with both groups. The control group was taught using the coursebook's two activities, while the experimental group was taught using additional activities and models. After the treatment, a post-test was given to both groups to determine the active-learning environment's effectiveness on the students' understanding of the concept of pressure. Interviews were also conducted with the experimental group. The post-test results showed a significant difference in favor of the experimental group. It was determined that students in both groups had misunderstandings of the topic before and after instruction. The interviews showed that the experimental group students perceive that the active learning environment facilitated better and easier learning. The conclusion that can be drawn is that the active learning environment was more effective for the students in the experimental group to learn about the concept of pressure.